Visualization of Hot Topics and Global Trends in Community Librarianship (With an Emphasis on the Role of Public Libraries) - Keshvari, Mariam; CheshmehSohrabi, Mehrdad (Public library quarterly (New York, N.Y.), 2024)
The general subject trends and emphasized points of Community Librarianship (CL) researches are not clear. According to reviewed papers, CL encompasses a wide range of social issues. This dispersion and diversity require presenting a comprehensive map of the thematic trends. The present study showed the concept of "social capital" is the underlying base for the literature of CL, which is the outcome of dialogue and interactive space of libraries. Also, historically, the related publications can be classified into five categories: 1) promoting the democratic culture and training informed and participating citizens 2) improving e-government; 3) library as a place for creating social capital; 4) sharing consumer health information; and 5) natural crises and disasters. The results of this study can show and reflect the "common good" of public libraries, that can effectively provide insight for librarians, attract policymakers' support, and maintain the position and future of these libraries.